Time course of performance changes and fatigue markers during training for the ironman triathlon - Joiner, Alexander Jason (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2010)
Suboptimal preparation for the Ironman triathlon can have detrimental effects on mental and physical condition. The purpose of this longitudinal investigation was to examine the relationship between a number of performance changes and fatigue markers during training for an Ironman as well as immediately after the event, in an attempt to better understand the effects of ultraendurance training. Eighteen athletes training for the Ironman; South Africa, 2009 were recruited for the study. Over the 6 month data collection period body mass, training load (TRIMP and Session x RPE methods), physiological responses (waking heart rate, postural dizziness, sleep ratings), changes in psychological state (profile of mood states - POMS), reported immunological responses (symptoms of illness), biochemical changes (salivary cortisol and alpha amylase) and performance (8 km submaximal running time trial (TT) and race day performance) were measured. These responses were compared to a control sample (n=15). Results show a significant increase (p<0.05) in training load (3899.4 ± 2517.8) four weeks prior to the event. Fatigue scores significantly increased (p<0.05) concurrently with this significant increase (p<0.05) in training. TT performance did not significantly (p<0.05) alter during the time course of training. It was however strongly correlated to training load (R2=0.85) and modestly related to race performance (R2=0.65). The signs and symptoms of upper respiratory tract infections (URTI) were prevalent during the training period, decreasing during the taper and race period. Large standard deviations were found within the majority of the responses. During the final two weeks of preparation, tension scores were significantly increased (p<0.05) while training load significantly decreased (p<0.05) during the final week of preparation. Cortisol increased significantly (p<0.05) immediately post race (0.507±0.15<g.DL-1) and 1.5 hours later (0.796±0.23<g.DL-1). Overall the results indicate that the POMS questionnaire was a sensitive marker of fatigue and stress associated with ultraendurance training, and that the event itself placed a great deal of stress on the athletes which was illustrated by the post event measures.
Keywords: Ironman triathlons -- Training; Physical education and training -- Physiological aspects; Endurance sports -- Training; Sports -- Physiological aspects; Fatigue